2015
DOI: 10.1002/pssb.201451366
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, thermal stability, and electrical transport properties of In/Sn codoped β‐Zn4Sb3 single crystal

Abstract: In and Sn codoped β‐Zn4Sb3 single crystals were prepared by a Sn‐flux method according to the formula Zn4.4Sb3Sn3Inx(x = 0–0.5). The thermal weight loss is suppressed completely until the melting point of the single crystals. All crystals exhibit p‐type conduction. The carrier mobility of the single crystals is increased, compared to a β‐Zn4Sb3 polycrystalline sample. All samples possess relatively high electrical conductivity, reaching 6.3 × 104 S/m for the sample with x = 0.18. The Seebeck coefficient is enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The highest value of 199 µV•K −1 is attained at 558 K for the x = 0.03 sample, which is comparable to previous reported values. [13,21] Then the Seebeck coefficient decreased with the increased Ge doping amount, presumably this behavior can be ascribed to the fact that the excessive Ge or the decrease of Sn have some influence on the band structure of the compounds.…”
Section: Electrical Transport Propertiesmentioning
confidence: 98%
See 1 more Smart Citation
“…The highest value of 199 µV•K −1 is attained at 558 K for the x = 0.03 sample, which is comparable to previous reported values. [13,21] Then the Seebeck coefficient decreased with the increased Ge doping amount, presumably this behavior can be ascribed to the fact that the excessive Ge or the decrease of Sn have some influence on the band structure of the compounds.…”
Section: Electrical Transport Propertiesmentioning
confidence: 98%
“…[11,12] In the past years, elements in the vicinity of Zn and Sb such as In, Pb, Sn, Cd, Bi, Mg, etc. were generally selected to dope the β -Zn 4 Sb 3 , [13][14][15][16][17][18][19][20] but Ge-substitution in β -Zn 4 Sb 3 has been rarely reported so far. Wang et al recently demonstrated the realization of a high thermoelectric figure of merit in Ge-substituted β -Zn 4 Sb 3 , the experimental results and theoretical calculations revealed that Ge substitution had a marked improvement on the Seebeck coefficient and the power factor.…”
Section: Introductionmentioning
confidence: 99%